PENGARUH KEPEMILIKAN MANAJERIAL, KOMITE AUDIT, DAN DERIVATIF KEUANGAN TERHADAP EFFECTIVE TAX RATE - Yensi, Yensi; Sandra, Amelia (Lembaga Penelitian dan Pengabdian kepada Masyarakat Institut Bisnis dan Informatika Kwik Kian Gie, 2019)
Tax for the company gives significant attention. Tax is seen as a burden that can reduce profit so the company will strive any efforts to pay tax at a lower cost. Meanwhile, the government considers tax as an important state income so that the government will draw tax as high as possible. To determine company effectiveness in managing tax, need a calculation. Measurement of effective tax planning can be done using the Effective Tax Rate. The differences ETR between companies can cause by several different factors. Therefore, this study aims to investigate several factors that influence ETR. The samples are manufacturing companies listed on the IDX period 2015-2017. The sampling technique is non-probability sampling using a purposive sampling method. This research used SPSS 20 with a quantitative analysis technique. The author uses the outlier method to improve data. There are 17 passed companies. The results of the F test indicate the independent variables simultaneously affected the dependent variable with a value of 0,000. The research showed the audit committee has a significant effect on ETR. Meanwhile, managerial ownership and financial derivative do not have a significant effect on ETR.Â Keywords: Effective Tax Rate, Managerial Ownership, Audit Committee, Financial Derivative